Evaluation of integrated management strategy for hydropower facilities operation - A. S. Lifar; A. E. Brom (Омский научный вестник)
The task of evaluating the integrated management strategy is solved for hydropower facilities in conditions of changing integrated management of the operation process. Despite the fact that the strategy is integrated, covers all business processes of operation, it is proposed to evaluate it for each of the indicators separately. The proposed method allows to visualize the results of the organization of operation processes and highlight the «bottlenecks».